HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH MELALUI PEMBERDAYAAN DAN PENGEMBANGAN SDM GURU DI SMK RIYADLUL ULUM EMBUNG TANGAR - Alimudin, Lalu; Hapipi, Hapipi (Penerbit Lafadz Jaya, 2024)
This research aims to explore the practice of empowering human resources, the leadership style of the school principal in empowering human resources, and the preferences of school members regarding the leadership of the principal in empowering human resources at SMK Riyadlul Ulum Embung Tangar. This research used a qualitative approach with an ethnographic design and was conducted at Riyadlul Ulum Embung Tangar Vocational School. Data collection was carried out through observation, interviews and documentation with source triangulation. Data analysis involves data collection, data reduction, data presentation, and conclusions. The results of the research show: (1) Empowerment of human resources is carried out through training and workshops for teachers as well as the implementation of minimum bachelor's degree requirements, (2) The leadership style of school principals tends to be democratic, and (3) The principal's leadership pays attention to welfare, input, as well as punishments for school members who violate them.